Valuing attributes of enhanced traffic information: An experience in Kolkata - Basu, Debasis; Maitra, Bhargab (Transport, 2007)
Most of the traffic information considers a single item like travel time or delay. In the present work, enhanced traffic information displaying instantaneous travel time and its variation from the previous interval to the present, is considered. An initial investigation is made on the effectiveness of such traffic information on route choice behavior of trip makers by valuation of attributes of the traffic information. Taking a case study of two urban corridors in the Kolkata metro city, India, the valuation is done separately for private car and taxi trip makers. The stated preference (choice based) data collected from trip makers are analyzed using both multinomial logit (MNL) and mixed logit (ML) modeling techniques. Assuming sparsely used constrained triangular distribution of random parameters, two different types of ML model are developed: one with independent choice sets and the other one by accounting heterogeneity around the mean of random parameter(s). Both family income and trip purpose are found to decompose heterogeneity around the mean estimate(s). The values of travel time and their variation presented in the paper encourage further investigation on such type of traffic information for management of congestion on alternative urban corridors both spatially and temporally.First Published Online: 27 Oct 2010